2021
DOI: 10.32598/immunoregulation.3.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils to Lymphocytes Ratio and the Prognosisof the COVID-19 Patients

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a new pandemic virus, a global concern, and has threatened human health. This virus binds to the Angiotensin-Converting Enzyme 2 (ACE2) that is expressed on different cells, especially on the alveolar cells. So the virus can enter the lung cells and causes respiratory syndromes. In Coronavirus Disease 2019 (COVID-19) that is caused by SARS-CoV-2, respiratory failure, and acute inflammation is the main cause of death. According to several reports,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…NLR has been thought to reflect the balance between the innate immunity of the acute inflammatory response as reflected by neutrophils, and adaptive immunity as reflected by lymphocytes. 22 In patients with COVID-19, there is a neutrophilic response with a simultaneous lymphopenia. While the neutrophilic response is the expected innate response, the lymphopenia is thought to be due to sequestration of T-cells in the infected lungs and virally mediated lymphocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR has been thought to reflect the balance between the innate immunity of the acute inflammatory response as reflected by neutrophils, and adaptive immunity as reflected by lymphocytes. 22 In patients with COVID-19, there is a neutrophilic response with a simultaneous lymphopenia. While the neutrophilic response is the expected innate response, the lymphopenia is thought to be due to sequestration of T-cells in the infected lungs and virally mediated lymphocyte apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a highly elevated NLR may represent a state of immunologic imbalance with unfavorable prognosis. 10,22 A meta-analysis of 10 published studies of pregnant women with COVID-19 found that 83.7% of cases had an elevated absolute neutrophil count, and 71.4% had a decreased absolute lymphocyte count. 26 Our data did not show an association of other inflammatory markers with disease severity.…”
Section: Discussionmentioning
confidence: 99%